Navigating the Cultural Maze in Program Planning for A Transnational Collaborative Initiative - Mazalan B. Kamis; Rosemary S. Caffarella; Mazanah Muhamad; Othman Omat (Adult Education Research Conference, 2006)
The purpose of this paper is to explore, through autobiographical narratives of each of the authors, the story of how this planning team navigated the cultural complexities in planning a transnational collaborative program involving two sites, one in the United States and another in Malaysia. More specifically, examples of specific ways of thinking and actions are provided that illustrate planning practices as related to five significant aspects of Malaysian culture
Keywords: Program planning; culture; transnational